Exploring the causal link between serum 25-hydroxyvitamin D concentrations and idiopathic sudden sensorineural hearing loss: Insights gained from a Mendelian randomization study involving two independent samples - Ying Zhao; Cong Yu; Hengchang Sun; Fangmei Xie; Jian Shen; Xiaoming Li; Xiaoyu Song; Wenfeng Luo; Jinhua He; Zeping Han (PLoS ONE, 2025)
Idiopathic sudden sensorineural hearing loss (ISSNHL) is defined by the rapid onset of hearing impairment without an identifiable etiology. The decreased serum concentrations of 25-hydroxyvitamin D(25(OH)D) was shown to be associated with decreased hearing ability. However, current cross-sectional studies have only demonstrated an association, failing to establish a causal link. Therefore, a comprehensive investigation is necessary to clarify the causal relationship between them. Analysis was done by using largescale genome-wide association analysis(GWAS) summary datasets to give information about the incidence of ISSNHL and genetically predicted serum 25(OH)D levels by a two-sample Mendelian randomization (MR) analysis. Instrumental variables (IVs) were identified as genome-wide significant single-nucleotide polymorphisms (SNPs) with a significance threshold of P < 1 × 10−8 and an independence criterion of r2 < 0.001. The GWAS data on serum 25-hydroxyvitamin D levels comprised 6,896,093 SNPs from 496,949 individuals of European ancestry (exposure variable). Outcome data were derived from another GWAS data, including 16,380,424 SNPs from 1,491 European ISSNHL cases and 196,592 controls. MR-Egger, inverse variance weighted (IVW), weighted median, simple mode, and weighted mode, were used to assess causal effects. Heterogeneity tests, horizontal pleiotropy tests, and the leave-one-out method were applied to evaluated the robustness of the MR analysis results. A total of 117 SNPs were employed as instrumental variables (P < 5 × 10−8). Our results indicated no causal association between serum 25(OH) D levels and the risk of ISSNHL within the European population (IVW; OR = 1.09, 95% CI = 0.81 to 1.48, P = 0.573). Furthermore, the statistical models did not reveal any evidence of heterogeneity or pleiotropy.